Outcomes with IV/oral Delafloxacin (DLX) Compared with Vancomycin/Aztreonam (VAN/AZ) in Treatment of Patients with Acute Bacterial Skin and Skin Structure Infections (ABSSSI) and Gram-positive (GP) Pathogens. (4th October 2017) - Overcash, Scott; O'Riordan, William; Lawrence, Laura; McCurdy, Sandra P; Tseng, Carol; Cammarata, Sue K
Abstract: Background: DLX, an novel anionic fluoroquinolone antibiotic, is in development for treatment of ABSSSI. This analysis focuses on the outcome in patients with Gram-positive (GP) pathogens including MRSA from 2 global phase 3 ABSSSI trials. Methods: Two double-blind trials of adults with ABSSSI randomized patients 1:1 to receive either q12h DLX IV/oral monotherapy or VAN 15 mg/kg with AZ for 5 – 14 days. Key endpoints were objective response at 48–72 hours; and investigator assessment of outcome based on resolution of signs and symptoms at Follow-up (FU day 14) and Late Follow-up (LFU day 21–28). Results: 1042/1510 patients enrolled had a baseline pathogen. 987 (95%) of patients with a baseline pathogen had a GP pathogen; 14% of patients had a mixed infection. Median erythema area at baseline was ~195 cm 2 . 30% had cellulitis, 31% abscesses, and 38% wounds. S. aureus was the most frequent isolate. The MIC50, MIC90 and MIC range for key pathogens were 0.008, 0.03, 0.002–0.5 µg/mL for MSSA; 0.12, 0.25, 0.002–4 µg/mL for MRSA; 0.015, 0.06, 0.008–0.06 µg/mL for S. pyogenes . Key endpoints are shown below: In the overall population, the proportion of patients with at least one treatment-emergent adverse event (AE) was similar for DLX (45.1%) compared with VAN/AZ (47.7%). The most frequent treatment-related AE were gastrointestinal in nature including nausea seen in 6.1% and 4.3%, and diarrhea seen in 6.1% and 2% of DLX and VAN/AZ patients, respectively. There were 0.8% of DLX patients and 2.4% VAN/AZ patients discontinued treatment due to treatment-related AEs. Conclusion: GP pathogens, particularly MRSA, are the most frequent pathogens in ABSSSI. Fixed dose DLX IV/oral monotherapy was comparable to VAN/AZ in patients with GP pathogens including MRSA based on the early objective response as well as investigator assessed response and microbiologic response. DLX appears effective and well tolerated in patients with GP pathogens in ABSSSI. Disclosures: S. Overcash, Melinta: Investigator, Research grant; W. O'Riordan, Melinta: Investigator, Research grant; L. Lawrence, Melinta: Employee, Salary; S. P. McCurdy, Melinta Therapeutics: Employee, Salary; C. Tseng, Melinta: Consultant and Research Contractor, Consulting fee; S. K. Cammarata, Melinta Therapeutics: Employee, Salary